2018
DOI: 10.1124/mol.118.111674
|View full text |Cite
|
Sign up to set email alerts
|

RGS10 Regulates the Expression of Cyclooxygenase-2 and Tumor Necrosis Factor Alpha through a G Protein–Independent Mechanism

Abstract: The small regulator of G protein signaling protein RGS10 is a key regulator of neuroinflammation and ovarian cancer cell survival; however, the mechanism for RGS10 function in these cells is unknown and has not been linked to specific G protein pathways. RGS10 is highly enriched in microglia, and loss of RGS10 expression in microglia amplifies production of the inflammatory cytokine tumor necrosis factor (TNF) and enhances microglia-induced neurotoxicity. RGS10 also regulates cell survival and chemoresistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…Consistent with these data, knockdown of RGS10 in BV2 cells enhances LPS-induced cyclooxygenase-2 (COX-2) expression and the release of its downstream effector, PGE2. Interestingly, amplification of LPS-stimulated TNF-α and COX-2 following microglial RGS10 suppression does not require Gαi activity [98]. Despite the importance of these results, the molecular mechanism underlying RGS10 regulation of microglial inflammatory signaling has not been clearly defined.…”
Section: Neuroinflammationmentioning
confidence: 92%
See 1 more Smart Citation
“…Consistent with these data, knockdown of RGS10 in BV2 cells enhances LPS-induced cyclooxygenase-2 (COX-2) expression and the release of its downstream effector, PGE2. Interestingly, amplification of LPS-stimulated TNF-α and COX-2 following microglial RGS10 suppression does not require Gαi activity [98]. Despite the importance of these results, the molecular mechanism underlying RGS10 regulation of microglial inflammatory signaling has not been clearly defined.…”
Section: Neuroinflammationmentioning
confidence: 92%
“…A recent study has demonstrated RGS10-mediated regulation of Inflammatory signaling in SKOV-3 ovarian cancer cells, where the expression of TNF-α and COX-2 is robustly enhanced following RGS10 knockdown compared to control cells. Interestingly, the effects of RGS10 suppression on TNF-α and COX-2 expressions are independent of amplified Gαi signaling [98]. Given the finding that RGS10 modulates survival and chemoresistance of ovarian cancer and regulates inflammatory mediators' expressions that have recently linked to ovarian cancer chemoresistance [126][127][128], further work is needed to investigate whether amplification of inflammatory signaling accounts for the enhanced survival and chemoresistance observed in RGS10-deficient ovarian cancer cells.…”
Section: Cancersmentioning
confidence: 99%
“…Further evidence of the potential for excessive NFκB activity to contribute to parkinsonian neurodegeneration comes from rodent and cell culture models deficient in the Regulator of G-Protein Signaling 10 (RGS10) [ 15 17 ]. RGS10 is highly expressed in central and peripheral myeloid cells where it acts as a negative regulator of inflammation through inhibition of NFκB activity [ 15 18 ]. These studies have shown that RGS10 loss globally, in microglia, in macrophages, and in neurons increases susceptibility to immune- and oxidative stress-mediated dopaminergic neurodegeneration [ 15 17 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another major finding from the present study was the identification of RGS10 as a novel target gene of miR-199b-5p. RGS10 is one of the smallest members of the RGS family and it exerts various biological effects in multiple organs ( 19 , 28 ). It has been reported that ovarian cancer cell apoptosis is decreased following RGS10 knockdown ( 29 ).…”
Section: Discussionmentioning
confidence: 99%